(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
This Research Includes The Definition Of The Manuscript (Explanation Of The Hajj) Of Sheikh Abi Abdullah Mohammed Bin Hassan Bin Masoud Al-Banani Fassi Moroccan Malki (T: 1194 E). The Researcher Identified This Manuscript To Clarify The Intellectual Heritage Of Our Scholars, As Well As To Motivate Universities And Science Students To Take Care Of Manuscripts And Serve Heritage In Their University Work. The Research Included An Introduction, Three Topics, And A Conclusion. The Research Also Produced Useful Results And Important Recommendations Related To The Subject.